Native universe : (National Museum of the American Indian, Smithsonian Institution, in association with National Geographic, 2004)
This gorgeous volume draws from the vast archives of the National Museum of the American Indian and the voices of some of the most prominent Native American scholars, writers, activists and tribal leaders. More than 300 full-color illustrations depict the artistry and culture of our hemisphere’s diverse indigenous peoples. With its insightful, firsthand prose, the book is a reminder that the ancient philosophies and folkways are just as valuable and relevant in today’s world as they were generations ago.